2019
DOI: 10.1155/2019/2357107
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Resting-State Functional MRI Activity of Frontostriatal, Thalamic, Temporal, and Cerebellar Brain Regions Differentiates Stroke Survivors with High Compared to Low Depressive Symptom Scores

Abstract: Background. One in three survivors of stroke experience poststroke depression (PSD). PSD has been linked with poorer recovery of function and cognition, yet our understanding of potential mechanisms is currently limited. Alterations in resting-state functional MRI have been investigated to a limited extent. Fluctuations in low frequency signal are reported, but it is unknown if interactions are present between the level of depressive symptom score and intrinsic brain activity in varying brain regions. Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…For example, Zhu and colleague (Zhu et al 2015) found that the change of regional properties of cortical networks are mainly concentrated on slow-5 band by using amplitude of low-frequency fluctuation (ALFF) and regional homogeneity (ReHo) methods. However, DC abnormalities in the subcortical structures and limbic system was not found in the slow-4 band in this study (Goodin et al 2019;Zuo et al 2010). Our study mainly investigated changes in the frequency-dependent effects on DC among acute BGIS patients, we speculate that the possible reason is that the interaction of the functional impairment and remodeling may not have fully developed in the early stage.…”
Section: Changes In Bgis Patients Are Frequency Specificmentioning
confidence: 56%
“…For example, Zhu and colleague (Zhu et al 2015) found that the change of regional properties of cortical networks are mainly concentrated on slow-5 band by using amplitude of low-frequency fluctuation (ALFF) and regional homogeneity (ReHo) methods. However, DC abnormalities in the subcortical structures and limbic system was not found in the slow-4 band in this study (Goodin et al 2019;Zuo et al 2010). Our study mainly investigated changes in the frequency-dependent effects on DC among acute BGIS patients, we speculate that the possible reason is that the interaction of the functional impairment and remodeling may not have fully developed in the early stage.…”
Section: Changes In Bgis Patients Are Frequency Specificmentioning
confidence: 56%
“… 5 In recent studies, it was reported that fALFF was sensitive to changes in post-stroke depressive symptom severity and implicated frontostriatal and cerebellar regions. 6 …”
Section: Discussionmentioning
confidence: 99%
“…The aberrant regional brain activity could be a more sensitive feature than lesion location and volume to characterize PSD in small samples ( Egorova et al, 2017 ). Another rs-fMRI study identified a significant correlation between PSD severity and fALFF in frontostriatal, temporal, thalamic, and cerebellar regions ( Goodin et al, 2019 ). These fMRI results also provided evidence for the role of the frontal-limbic system in PSD.…”
Section: Regional Structural and Functional Abnormalities And Poststr...mentioning
confidence: 99%